Economic burden of paediatric-onset disabilities among young and middle-aged adults in the USA: a cohort study of privately insured beneficiaries. Issue 9 (3rd September 2019) - Whitney, Daniel; Kamdar, Neil; Hirth, Richard A; Hurvitz, Edward A; Peterson, Mark D
Abstract : Objective: Individuals with paediatric-onset disabilities (PoDs) have complex healthcare needs and are susceptible to adverse health outcomes, which may impose a higher strain on healthcare resources. The burden of healthcare resource utilisation and costs attributed to the population of adults with PoDs is not clearly established. The objective here was to compare healthcare resource utilisation and costs between adults with versus without PoDs. Design: Cohort. Setting: Data were from the 2016 Optum Clinformatics Data Mart, a de-identified nationwide claims database of beneficiaries from a single private payer in the USA. Participants: International Classification of Diseases, Tenth Revision, Clinical Modification diagnosis codes were used to identify beneficiaries with PoDs that were between 18 and 64 years of age. Primary and secondary outcome measures: Annual all-cause healthcare resource utilisation and total healthcare costs were compared between adults with and without PoDs before and after adjusting for sociodemographics and several costly non-communicable diseases. Results: Adults with PoDs (n=121 446) had greater annual mean counts of service utilisation for all service types (eg, inpatient, outpatient, emergency visits) compared with adults without PoDs (n=5 415 475) before and after adjustments (all p<0.001). Adults with PoDs had greater unadjusted total standardised reimbursement costs (US26 702 vs US8464; mean difference=US18 238; cost ratio (CR)=3.16; 95% CI=3.13 to 3.18) and total patient out-of-pocket costs (US2226 vs US1157; mean difference=US1069; CR=1.88; 95%CI=1.86 to 1.89). After adjustments, total standardised reimbursement costs were 2.32 times higher (95% CI=2.30 to 2.34) and total patient out-of-pocket costs were 1.65 times higher (95% CI=1.64 to 1.66) compared with adults without PoDs. Conclusion: Adults with PoDs had greater healthcare utilisation and costs, even after accounting for costly diseases. Future research is needed to identify the cost drivers for adults with PoDs.